The Condition of Academic Administration in the New Normal of Schools under the Office of Nonthaburi Primary Educational Service Area 2 - Jaisiri , Chutimon; Niyamajan , Ratikorn; Thongmeesri, Sirirat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were; 1) to study school academic administration based on the New Normal, 2) to compare school academic administration based on the New Normal, and 3) to study the guidelines of school academic administration based on the New Normal under Nonthaburi Primary Educational Service Area Office 2. The samples consisted of 317 educational personnel and teachers who were involved in academic administration under Nonthaburi Primary Educational Service Area Office 2. The research instruments used in this study were a 5-level rating scale questionnaire with a 0.98 confidence value, and the interview forms of school academic administration based on the New Normal under Nonthaburi Primary Educational Service Area Office 2. The descriptive statistics used for data analysis were mean, standard deviation, and content analysis. The results showed that 1) overall and parts of school academic administration based on the New Normal conditions under Nonthaburi Primary Educational Service Area Office 2 was at a high level. When considering each aspect, it was found that the highest level were: the internal quality assurance system and educational standards, educational measurement and evaluation, and transfer of grade and education supervision. The lowest level aspect was research for education development in schools. 2) the result of comparing school academic administration conditions based on the New Normal under Nonthaburi Primary Educational Service Area Office 2 classified by school sizes found that they were not different, and 3) the guidelines of school academic administration based on New Normal under Nonthaburi Primary Educational Service Area Office 2 in terms of research for improving the quality of education in school, there should be more cooperative planning and clear setting plans. In terms of promoting the community to strengthen academics, the stakeholders should understand the importance of and plan together between the school and the community. In terms of guidance, they should be carried out continuously and systematically.